In Vitro Repression of the Transcription of gal Operon by Purified gal Repressor - Nakanishi, Shigetada (National Academy of Sciences, 1973)
We have studied the in vitro repression of gal mRNA synthesis by the gal repressor from Escherichia coli. By use of a four-step purification procedure involving chromatography on phosphocellulose, DEAE-cellulose, and an affinity resin, the gal repressor has been purified about 1600-fold from a crude cell extract. The purification was aided by use of a cell extract made after prophage induction of cells lysogenic for bacteriophage λ that carries the gal repressor gene (galR). The highly purified gal repressor is an effective and specific repressor of in vitro synthesis of gal mRNA with λ gal DNA as template. Both D-fucose and D-galactose overcome the action of gal repressor; the half-maximal concentrations of D-fucose and D-galactose for overcoming the action of repressor are 1 mM and 0.5 mM, respectively. The repressor fails to repress gal-specific transcription when the gal DNA contains a cis-dominant operator constitutive (O(c)) mutation. We conclude that the gal repressor recognizes the gal operator site and acts by preventing gal transcription.